2009
DOI: 10.2337/db07-1438
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Derived Angiopoietin-Like Protein 4 Is Induced by Fatty Acids via Peroxisome Proliferator–Activated Receptor (PPAR)-δ and Is of Metabolic Relevance in Humans

Abstract: OBJECTIVE— Long-chain fatty acids (LCFAs) contribute to metabolic homeostasis in part via gene regulation. This study's objective was to identify novel LCFA target genes in human skeletal muscle cells (myotubes). RESEARCH DESIGN AND METHODS— In vitro methods included culture and treatment of human myotubes and C2C12 cells, gene array analysis, real-time RT-PCR, Western blotting, ELISA, chromatin immunoprecipitation, and RNA interference. Human subjects (two cohorts) were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 49 publications
(47 reference statements)
11
143
1
Order By: Relevance
“…There are several basic residue-rich regions in ANGPTL 3 and 4, both in N-and C-terminal regions that could mediate the binding of these proteins at the sites important for LPL activity. For ANGPTL3, good agreement with previous reports showing that ANGPTL3 is present in the circulation at a higher concentration (224 ng/ml) compared with ANGPTL4 (1.73 ng/ ml) ( 22,23 ). Although some differences exist in the values reported for ANGPTL 3 and 4, these probably are due to differences in method standardization, population samples, and/or the antibodies used.…”
Section: Effect Of Heparin On Human Angptl 3 and 4 In Vivo And In Vitrosupporting
confidence: 76%
“…There are several basic residue-rich regions in ANGPTL 3 and 4, both in N-and C-terminal regions that could mediate the binding of these proteins at the sites important for LPL activity. For ANGPTL3, good agreement with previous reports showing that ANGPTL3 is present in the circulation at a higher concentration (224 ng/ml) compared with ANGPTL4 (1.73 ng/ ml) ( 22,23 ). Although some differences exist in the values reported for ANGPTL 3 and 4, these probably are due to differences in method standardization, population samples, and/or the antibodies used.…”
Section: Effect Of Heparin On Human Angptl 3 and 4 In Vivo And In Vitrosupporting
confidence: 76%
“…4B and 7). Consistent with the immunoblot results were no meaningful differences in the mRNA levels of the PPAR target genes CPT1, MCAD, AOX and FABP1 [22][23][24][25], the PPAR/ target genes pyruvate dehydrogenase kinase (PDK) 4 and angiopoietin-like protein 4 (ANGPTL4) [26,27], or the PPAR target genes FABP4 and fat-specific protein 27 (FSP27) [28,29] among the groups ( Fig. 2 and Supplementary Fig.…”
Section: Hepatic Expression Of Ppars and Rxrsupporting
confidence: 71%
“…Though hnf4a mutant zebrafish have reduced in3.4 activity in the intestinal epithelium based on transgenic reporter assays, the transcript levels of the endogenous zebrafish angptl4 gene appears unaffected in both larval digestive tracts and adult IECs. The zebrafish genome encodes two additional HNF4 family members (hnf4b, hnf4g), and previous studies in mammals have shown Angptl4 can be regulated by other metabolically activated nuclear receptors (Staiger et al 2009;Korecka et al 2013). We hypothesize that loss of HNF4A function may lead to a metabolic imbalance leading to atypical or compensatory activation of other trans-and cis-factors that control expression of angptl4 and other genes in the intestine.…”
Section: Discussionmentioning
confidence: 99%